Cholesteatoma Clinical Outcome and Complications: A Study on Patients with Chronic Ear Disease (Medical Forum Monthly, 2024)
Objectives: To identify the clinical behaviour and consequences of cholesteatoma and to formulate a strategy for achieving early diagnosis, appropriate management and avoidance of all the grave complications.Study Design: Hospital based descriptive type of studyPlace and Duration of Study: This study was conducted in Shahina Jamil Hospital from April 2011 to Dec 2012.Materials and Methods: 40 patients of any age and gender were included in the study. The age, gender, socio-economic status and complications like hearing loss, facial nerve paralysis, intracranial spread, labyrinthitis, mastoid fistula and ossicular chain status were recorded and analyzed.Results: We found that 62.5% were male and 37.5% were female.75% of the patients belong to rural areas and 25% belong to urban areas. All the patients (100%) presented with ear discharge and hearing loss. Ossicles were found intact in all patients. Labyrinthitis was the most common complication (37.5%).Conclusion: It was found that cholesteatoma was frequent among poor, male and young patients leading to necrosis of the ossicles in all patients. Labyrinthitis, mastoid fistula and intracranial spread were common complication.